Analisis Kebijakan pengadian Mahasiswa Pendidikan Ulama Tarjih Muhammadiyah Yogyakarta - Fajar Al-Mahmudi (FAI UMY, 2017)
Analisis Kebijakan pengadian Mahasiswa Pendidikan Ulama Tarjih Muhammadiyah Yogyakarta